Development of Microemulsion Delivery System of Essential Oil from Zingiber cassumunar Roxb. Rhizome for Improvement of Stability and Anti-Inflammatory Activity - Wantida Chaiyana (2018)
© 2016 American Association of Pharmaceutical Scientists The present study aims to investigate the major constituents of the essential oil from Zingiber cassumunar rhizome (EO) and to develop microemulsions with enhanced chemical stability and anti-inflammatory activity of EO. The major constituents of EO were terpinen-4-ol (40.5 ± 6.6%) and sabinene (17.4 ± 1.4%) as determined by gas chromatography–mass spectrometry. These compounds were responsible for the anti-inflammatory activities of EO. Sabinene and terpinen-4-ol significantly reduced nuclear factor-kappa B (NF-kB) expression by 47 ± 5 and 78 ± 8%, respectively (p < 0.001) and significantly reduced the interleukin-6 (IL-6) secretion levels to 64 ± 4% (p < 0.05) and 50 ± 1% (p < 0.001), respectively. EO microemulsions, developed using the system of EO/Tween 20 and propylene glycol (2:1)/water, showed the internal droplet size in the range of 211.5 ± 63.3 to 366.7 ± 77.8 nm. Both EO and EO microemulsions were shown to be safe for human use since there was no apparent toxic effect on human peripheral blood mononuclear cells. Interestingly, EO microemulsion could significantly protect sabinene from the evaporation after heating–cooling stability test, which leads to a good stability and high efficacy. Moreover, EO microemulsions significantly enhanced the anti-inflammatory effect comparing to the native EO. Therefore, microemulsions were attractive delivery system for natural anti-inflammatory compounds since they could enhance both efficacy and stability of EO.